Mpox in sports: A comprehensive framework for anticipatory planning and risk mitigation in football based on lessons from COVID-19 - Chamari, Karim; Ben Saad, Helmi; Dhahbi, Wissem; Washif, Jad; El Omri, Abdelfatteh; Zmijewski, Piotr; Dergaa, Ismail (Biology of Sport, 2024)
The World Health Organization’s declaration of mpox (formerly known as monkeypox) as a public health emergency of international concern (PHEIC) in July 2022, followed by its resurgence in 2024, has sparked concerns about its potential impact on sports, especially contact sports such as football. Although mpox is not a pandemic (as of late September 2024), the coronavirus disease 2019 (COVID-19) experience offers valuable lessons for proactive planning in sports. Our conceptual framework has been designed to draw insightful lessons from the COVID-19 pandemic to assist sports organizations in planning for and preventing similar situations. We aimed to draw lessons from COVID-19 to help sports organizations enhance practical preparedness through effective planning and mitigation strategies. Accordingly, we sought to assess the potential impact of mpox on sports, with a focus on football (soccer), and to develop strategies for prevention, management, and preparedness based on epidemiological insights and lessons from COVID-19 pandemic experience. Here we review mpox’s pathophysiology and possibility of transmission in sports settings and discuss tailored strategies, including risk assessments, testing protocols, hygiene measures, and return-to-play policies. This review highlights key differences between mpox and COVID-19 in transmission, incubation, and management, emphasizing the need for customized prevention and control measures in sports. We propose innovative risk assessment methods using global positioning system tracking and machine learning for contact analysis, alongside tailored testing and hygiene protocols. We emphasize the importance of proactive planning, noting improved preparedness in the sports community compared to the early days of COVID-19. In conclusion, our proposed framework provides sports organizations with practical tools to manage potential risks associated with mpox, ensuring the continuity of activities while prioritizing public health.